The Agreement Rate between Radiographic Interpretation and Histopathologic Diagnosis of Jaw Lesions - Soulafa Almazrooa; Nada O. Binmadi; Hanadi M. Khalifa; Fatima M. Jadu; Ahmed M. Jan; Dalia E. Meisha (Radiology Research and Practice)
Background. To determine the agreement rate between histopathologic diagnosis and radiographic interpretation of jaw lesions. Methods. Cases with jaw pathologies that have diagnostically adequate histopathologic samples and radiographic examinations were reviewed retrospectively. Two board-certified oral and maxillofacial pathologists (OMFP) independently determined the histopathologic diagnosis, while two board-certified oral and maxillofacial radiologists (OMFR) determined the radiographic interpretations independently. Then the histopathologic diagnosis and the radiographic interpretation were compared for agreement. Results. A total of 104 cases (53% females) were included with a mean age of 31 years. The agreement rate between histopathologic diagnosis and radiographic interpretation was 49%. OMFP required OMFR consultations to reach a diagnosis in 16% of cases. The most commonly encountered lesions were by far odontogenic cysts of inflammatory origin and the agreement for this disease category was 49.1%. However, agreement rates were highest for the disease category of tumors (62.5%). Conclusion. The agreement rate between OMFP and OMFR was higher for tumors than cysts. Agreement rates between OMFP and OMFR improved with efficient consultation between the two disciplines.